An MILP model for optimization of a small-scale LNG supply chain along a coastline. (15th January 2015) - Jokinen, Raine; Pettersson, Frank; Saxén, Henrik
Highlights: A model for optimizing small-scale LNG supply chains is presented. The model minimizes total costs associated to fuel procurement. The use of the model is illustrated by a case study which considers an LNG supply chain in Finland. The model provides valuable information to aid in LNG supply chain design decisions. Abstract: The world energy demand is continuously increasing and natural gas is one of the strongest candidates to cover the growth. However, natural gas is unavailable in many energy intensive areas and the best way to introduce natural gas to new, scattered, areas is by transporting it as liquefied natural gas (LNG). LNG can be shipped from a large LNG import terminal to consumers through a network of smaller satellite terminals with a combination of sea- and land-based transports. Building up a small-scale supply chain network is expensive and capital intensive. This paper presents a mathematical model to aid in the supply chain design decisions by minimizing the total costs associated with fuel procurement. The use of the model is illustrated by a case study, where the optimal supply chain of LNG for covering certain parts of the energy requirements of a country is designed under different cost structures for LNG and for its land-based transportation.